KOMPETENSI GURU DALAM MENYUSUN BUTIR SOAL PADAMATA PELAJARAN BAHASA JAWA DI SEKOLAH DASAR - Mujimin, - (Lembaran Ilmu Kependidikan, 2010)
Kata kunci:Amultiple choice is a kind of test in which answers can be chosen from some availableanswers.Amultiple choice consists of a stem and some choices. The answers consistof a correct answer and some distracters. The correct answer must be the right one,while the distracters are the incorrect ones. The distracters must work as a trap. Itmeans that the students might choose these distracters if they do not master thematerial.This research describes the ability of teachers to create final test of Javanese Languagelesson in an Elementary School. The data were analyzed quantitatively andqualitatively. Qualitative technique was related to the form of the test before beingtested, while the quantitative technique was related to the result of the test.The ability of teachers in making the final test of Javanese Language lesson in theElementary School in the academic year of 2008/2009 in Banyumanik district waspoor. It was indicated by the test that was no proportional in terms of its degree ofdifficulties and the differential level.Kata Kunci : penyusunan, butir soal, ujian akhir sekolah